Lipid Profile and Insulin Resistance in Patients with Type-ΙΙ Diabetes Mellitus - Walid, Hadil; ali, Layla; Atiyah, majeed; Abdullah, awaz (Iraqi National Journal of Nursing Specialties, 2010)
Objective: To investigate the relation between dyslipidemia and insulin resistance where it is one of the metabolicdisorders in patients with type-ΙΙ diabetes mellitus and compare the results with the control group.Methodology: Blood samples were collected from (35) patients with type-ΙΙ diabetes mellitus, besides (35) healthyindividuals as a control group were enrolled in this study. The age of all subjects range from (20-50). Serum wasused in determination of glucose, insulin, lipid profile (cholesterol (Ch), triglyceride (TG), high-density lipoprotein(HDL-Ch), low-density lipoprotein (LDL-Ch) and very low-density lipoprotein (VLDL), for patients and controlgroups. Insulin resistance (IR) was calculated according to homeostatic model (HOMA-IR).Results: The results revealed a statistically significant elevation levels (P